EFEKTIVITAS PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN QUANTUM TEACHING DI KELAS VIII SMP - Hapsari, Tiara (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to determine the effectivity of learning mathematics using Quantum Teaching approach in matter of Linear Equations Systems in Two Variables at Class VIII Junior High School 5 Pontianak. This method used the experimental method. The results showed 1) Students activities classified as high at 67.83%, 2) There is a difference with students learning completenes in classical as evidenced by the results of t-test analysis that shows mastery students > 75% at a significance level of 5%, and 3) There is a difference learning outcomes between the experimental class and control class as evidenced by the Mann-Whittney test obtain sig 0.001 < 0.05. So, learning mathematics by Quantum Teaching approach in the matter of Linear Equations Systems of Two Variables in class VIII SMP Negeri 5 Pontianak is effective by aspects of the students by looking at the learning activity, learning completeness the of the students, and the differences in learning outcomes. Keywords: Effectivity of Learning, Quantum Teaching,Â  Students Activities, Students Completenes